A morphometric and molecular study of the apoptosis observed on tadpoles' tail explants under the exposition of triiodothyronine in different homeopathic dilutions. Issue 3 (August 2016) - Guedes, José Roberto Pereira; Carrasco, Solange; Ferreira, Cláudia M; Bonamin, Leoni V; Goldenstein-Schainberg, Cláudia; Martins, Vanessa; Capelozzi, Vera L
Abstract : Background: As a therapeutic system, homeopathy is supported by: i) similitude and experimentation in healthy individuals, ii) potentization. A challenge for researchers consists in looking for signals in water (or vehicle) to explain the storage of information in extremely high dilutions and the transfer of such information to the living systems. Anuran amphibian metamorphosis is controlled by thyroid hormones (TH), including the resorption of the tadpole tail. Apoptosis is a genetically regulated form of cell death that can be triggered by various extracellular and intracellular stimuli resulting in coordinated activation of a family of cysteine proteases called caspases. Methods: This study was blind and randomized. It performed in three stages: I) the identification of the most effective T3 homeopathic dilution to induce apoptotic reactions in Rana (Lithobates) catesbeianus tadpole tail explants stimulated by T3 in substantial, II) study of different controls and III) detection in explants under the action of the most effective dilution of T3, as established in Stage I. Results: There was no statistically significant difference between tail macroscopic dimensions between the groups. T3 10cH decreased the expression of caspase 3/7 mRNA, in explants treated with T3 20 nM. Conclusion: The present experiment is in agreement with the hypothesis that T3, at a 10cH homeopathic dilution, changes the metamorphosis molecular network. Highlights: Study of apoptotic changes induced by triiodothyronine 20nM in bullfrog tadpoles tail explants under the action of T310cH. T310cH decreases the expression of caspase 3/7 mRNA, on explants that were under the molecular action of T3 20 nM. This experiment is in agreement with the hypothesis that T310cH would be able to change the metamorphosis molecular network.